The Influence of Service Quality, Professionalism of Work, and Promotion on Customer Satisfaction of Bank Jatim Branch of Dr. Soetomo Hospital Surabaya - Farah Nurmalia Damayanti; Joko Suyono; Arasy Alimudin (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
This research is motivated by the idea that banks must increase customer satisfaction. Many benefits received with high customer satisfaction, including increasing customer loyalty, increasing advertising effectiveness, and increasing business reputation The purpose of this study is to analyze the effect of service quality, work professionalism and promotion on customer satisfaction. The population in this study was 2,155 customers, the number of samples using the Slovin formula was 96. The data analysis technique used was multiple regression analysis. The research results are: 1) There is an influence of service quality on customer satisfaction, 2) There is the influence of work professionalism on customer satisfaction, 3) There is an effect of promotion on customer satisfaction, 4) There is the influence of service quality, work professionalism and promotion of customer satisfaction, 5) Variable work professionalism has a dominant influence on customer satisfaction.